'Auja el-Foqa: a desert fortress on ancient Israel's eastern frontier - Ben-Shlomo, David (The Biblical archaeology review, 2021)
Overlooking the Jordan Valley and Jericho, the site of ‘Auja el-Foqa stood on ancient Israel’s eastern frontier. Archaeologists have uncovered the remains of an Israelite or Judahite fortress. Have they found biblical Na‘arah?